Structure elucidation off seven steroids from Sinularia conferta. - Ngoc, Ninh Thi; Mai Huong, Pham Thi; Phuong Chi, Nguyen Thi; Thung, Do Cong; Cuong, Nguyen Xuan; Thanh, Nguyen Van; Nam, Nguyen Hoai; Minh, Chau Van (Vietnam Journal of Chemistry, 2017)
Seven steroids were isolated from the methanol extract of the soft corals Sinularia conferta. These steroids were elucidated as 7a-methoxyergosta-5,24(28)-diene-3b-ol (1), ergosta-5-ene-3β,7α-diol (2), 3β,7α-dihydroxyergosta-5,24(28)-diene (3), 3β-hydroxyergosta-5,24(28)-diene-7-one (4), ergosta-24(28)-ene-3β,5α,6β-triol-6-acetate (5), ergosta-24(28)-ene-3β,5α,6β-triol (6), and ergosta-3β,5α,6β-triol (7) by 1D and 2D-NMR experiments and comparison with reported data. Keywords. Sinularia conferta, Alcyoniidae, soft coral, steroid.